2005
DOI: 10.1016/j.clpt.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic-pharmacodynamic model for the quantitative prediction of dofetilide clinical QT prolongation from human ether-a-go-go-related gene current inhibition data

Abstract: The current mechanism-based pharmacokinetic-pharmacodynamic model quantified the relationship between in vitro hERG channel blockade and clinical QT prolongation for dofetilide. This model may prove valuable for assessing the risk of QT prolongation in humans for other drugs that selectively block the hERG channel on the basis of in vitro assays and pharmacokinetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 28 publications
(35 reference statements)
5
67
0
Order By: Relevance
“…For each antibiotic studied, hERG current inhibition was measured (n ϭ 4 -5 cells) at concentrations ranging from 10 to 300 M. Drugs were perfused in the experimental chamber in a cumulative manner, and dose-response relationships were determined by fitting the data with a Hill equation to obtain inhibitory concentration values of 20 and 50% (IC 20 and IC 50 ). Although hERG IC 50 values are traditionally used for comparison of data, previous studies by our group (Fossa et al, 2004) and others (Redfern et al, 2003;Jonker et al, 2005) have shown that clinically significant prolongation of the QT interval is generally associated with inhibition of hERG current amplitude ranging from 10 to 20%. The IC 20 and IC 50 values determined for the three antibiotics studied were moxifloxacin, 31 and 102 M, erythromycin, 21 and 96 M, and telithromycin, 11 and 46 M, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For each antibiotic studied, hERG current inhibition was measured (n ϭ 4 -5 cells) at concentrations ranging from 10 to 300 M. Drugs were perfused in the experimental chamber in a cumulative manner, and dose-response relationships were determined by fitting the data with a Hill equation to obtain inhibitory concentration values of 20 and 50% (IC 20 and IC 50 ). Although hERG IC 50 values are traditionally used for comparison of data, previous studies by our group (Fossa et al, 2004) and others (Redfern et al, 2003;Jonker et al, 2005) have shown that clinically significant prolongation of the QT interval is generally associated with inhibition of hERG current amplitude ranging from 10 to 20%. The IC 20 and IC 50 values determined for the three antibiotics studied were moxifloxacin, 31 and 102 M, erythromycin, 21 and 96 M, and telithromycin, 11 and 46 M, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It should, however, be acknowledged that QT prolongation is found in humans at estimated free concentrations of PQP which are 10 times lower (0.008 M) than those which block 50% of hERG activity in vitro (0.087 M). A possible explanation for this discrepancy is that QT prolongation in vivo may occur at levels of hERG blockade in the 10% range (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, the inhibition of the potassium current I inhib ij relative to the i-th cell and the j-th observation was modelled according to [39], that is…”
Section: In Vitro Analysis Herg Current Inhibitionmentioning
confidence: 99%
“…Therefore, besides the assessment of the relationship between dogs and humans in terms of QTinterval prolongation via the development of a population PK/PD model, an operational PK/PD model of pharmacological agonism [38,39] is implemented in order to evaluate the possible connection between the percent inhibition of the human ether-a-go-go-related gene (hERG) and the increase in the QT interval. In particular, in preclinical studies, the hERG assay is widely used to assess the drug effect on the inhibition of the current through the potassium channels (IKr) in cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation